Deficit Irrigation Provides a Trade-Off Between Water Use and Alfalfa Quality - Yadong Wang; Qiuchi Zhang; Kai Gao; Liliang Han; Xingfu Li; Jing He; Derong Su (Agronomy)
Currently, the world is facing a serious agricultural water crisis, which also affects grassland areas. Alfalfa, a key perennial forage legume, consumes about 10% of China’s pastoral irrigation water. Reducing irrigation generally results in a loss of hay yield, but the effects on alfalfa quality and its relationship to water use are less clear. In this study, we explore alfalfa quality under different irrigation deficits and its relationship to water use in the Hexi Corridor of China. Alfalfa water use, quality yield (relative feeding value yield (RFVyield) and crude protein yield (CPyield)), and quality water use efficiency (relative feeding value water use efficiency (WUERFV) and crude protein water use efficiency (WUECP)) were measured in a field experiment. Alfalfa quality showed a negative correlation with the irrigation quota (the determination coefficient for relative feeding value was 0.375 and for crude protein was 0.289). There was a positive correlation between quality yield and irrigation quota (the determination coefficient for RFVyield was 0.570 and for CPyield was 0.631). The higher irrigation quota increased quality yield, which compensated for its negative effects on alfalfa quality. The mild and moderate water deficit treatments showed lower WUERFV than both the severe and no water deficit treatments. Moderate or mild water deficit is recommended to be used for one-year-old alfalfa treatment. No water deficit is beneficial to improve the quality water use efficiency of two-year-old alfalfa.